Patients' understanding of clinical research: An Italian cancer patient survey. Issue 1 (February 2019) - Rudnas, Britt; Montanari, Emanuela; Dall'Agata, Monia; Petracci, Elisabetta; Nanni, Oriana
Introduction: Patients' awareness of clinical research and their involvement in clinical trials is of great importance, but it is difficult to estimate the extent of knowledge on the research being undertaken. Methods: We evaluated the level of knowledge about clinical research using a self-reporting survey distributed to 967 adult patients with cancer attending the Departments of Medical Oncology and Onco-Haematology Units of IRST IRCCS and 4 hospitals in the region of Emilia-Romagna, Italy. The questionnaire was composed of 10 specific items on research knowledge. Patients responding correctly to at least 8 of the 10 items were considered to have a good understanding of clinical research. Results: The questionnaire was completed by 769 patients (response rate 79.5%). Only 19% of patients were found to have a good understanding of clinical research. Patients with higher education and those who had previous clinical trial experience showed a significantly better understanding. Fifty-three percent of patients said that they would be willing to participate in a trial studying a new drug and 75% expressed an interest in taking part in informative meetings/events about clinical studies. Conclusions: Our results show that patients' understanding of clinical research is limited and highlight an interest in learning more.